HUBUNGAN PEMBERIAN ASI DENGAN KEJADIAN HIPERBILIRUBINEMIA PADA NEONATUS DI RUANG PERINATOLOGI RS Tk.II UDAYANA - Ni Made Ari Sukmandari; Komang Yogi Triana; Ayu Nanda Rosma Dewi (JURNAL MEDIKA USADA, 2023)
Jaundice is one of the most common clinical phenomena found in newborns, which can occur physiologically or pathologically. The high incidence of hyperbilirubinemia in the Perinatology Room of Rs Tk.II Udayana caused by the lack of breastfeeding in neonates can cause the baby to fall into a deteriorating condition and even neonatal death can occur. The purpose of this study was to determine the relationship between breastfeeding and the incidence of hyperbilirubinemia in neonates in the Perinatology Room of Rs Tk.II Udayana. This research is a quantitative research using correlational method with cross sectional approach. Sampling used a non-probability sampling technique, namely accidental sampling as many as 26 people. The research data were analyzed using chi square. Univariate test results showed that most of the respondents were breastfed as many as 16 people (61.5%) and most of the respondents experienced hyperbilirubinemia as many as 14 people (53.8%). The results of the bivariate test of this study were tested with the chi square statistical test, the -value was obtained. = 0.001 <alpha (0.05) it can be concluded that there is a relationship between breastfeeding and the incidence of hyperbilirubinemia in neonates in the Perinatology Room of Rs Tk.II Udayana. This research is expected to be useful to add insight into the importance of breastfeeding for newborns.